RACISM IN UNITED STATES OF AMERICA REFLECTED IN THE FILM “TILL” (2022) - Rahmawati, Fatikha; Hidayah, Atinia (Language and Literature Faculty, Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2024)
This study is aimed at analyzing how racism is generally represented in the film “Till” (2022) and how forms of racial discrimination violate human rights in the film “Till” (2022) and leave deeply felt feelings. The researcher uses the qualitative method to analyze the film “Till” (2022), directed by Chinonye Chukwu, as objective research. The approach and theory that the researcher uses to analyze the data are based on Miles & Brown's (2003) theory of racism. This study shows that racial discrimination issues in daily life can happen in many places and in any circumstance. Everyone in African America can experience it. In extreme situations, white people can murder brutally anyone who is the object of discrimination, regardless of age. It is racial discrimination that leaves deep wounds, such as trauma. On the other side, it became brave to oppose racism.